Differential Sandwich Theorems For Certain Analytic Functions. - M. Ali, Rosihan; Ravichandran, V.; Hussain Khan, M.; Subramanian, K. G. (Pushpa Publishing House., 2004)
We give some applications of first order differential super ordinations to obtain sufficient conditions for normalized analytic functions f(z) to satisfy